2022
DOI: 10.1111/rda.14175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fortification of extender with α‐terpineol and rosemary essential oil on post‐thaw ovine semsen quality

Abstract: The goal of the present study was to assess the viability of the cryopreserved ovine (Ovis aries) semen, upon supplementation with α-terpineol and rosemary essential oil (Rosmarinus officinalis). The collection of the semen from six rams formed the pool, collected once a week during 7 weeks. The diluted semen was packed into straws (0.25 ml) and frozen in a TK 3000® device. Both α-terpineol and rosemary essential oil were added in the concentrations of 6.25, 12.5 and 25 μg/ml to the TRIS-yolk extender forming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Motlagh et al (2014) found that a 2% rosemary extract in the ram semen extender improved sperm parameters and reduced MDA levels. Bezerra et al (2022) discovered that a 12.5 μg/mL concentration of rosemary extract increased sperm motility, improved membrane integrity at 25 μg/mL, and enhanced acrosome integrity at 6.25 μg/mL after thawing. Moreover, Diab et al (2021) demonstrated that the use of 20 mg of rosemary extract in the ram semen extender at 37 and 5°C improved motility, live sperm count, and reduced abnormality rates.…”
Section: Some Herbal Extracts Containing Antioxidantmentioning
confidence: 99%
“…Motlagh et al (2014) found that a 2% rosemary extract in the ram semen extender improved sperm parameters and reduced MDA levels. Bezerra et al (2022) discovered that a 12.5 μg/mL concentration of rosemary extract increased sperm motility, improved membrane integrity at 25 μg/mL, and enhanced acrosome integrity at 6.25 μg/mL after thawing. Moreover, Diab et al (2021) demonstrated that the use of 20 mg of rosemary extract in the ram semen extender at 37 and 5°C improved motility, live sperm count, and reduced abnormality rates.…”
Section: Some Herbal Extracts Containing Antioxidantmentioning
confidence: 99%